Improvement to the physical quality and imbibition pattern in seeds of candeia (Eremanthus incanus (Less.) Less.) - Davide,Antonio Cláudio (2011)
The objective of this work was to develop a methodology for seed processing and X-ray analysis and to study imbibition pattern in seeds of candeia (Eremanthus incanus). Seeds were gathered in 2001 and 2002 in Morro do Pilar and Lavras respectively, processed and stored in a cold chamber (5ºC/60%RH) until the start of experiments. In order to identify unfilled seeds, a protocol was developed for X-ray use combining radiation energy (Kv) and exposure time (seconds). For elimination of unfilled seeds, an experiment was conducted using a South Dakota seed blower whereby different opening settings and ventilation times were combined. Original seed lots and categorized lots following radiograph viewing were tested by germination tests, with seeds being cleansed in sodium hypochlorite and scattered over blotting paper in 'gerboxes' and then taken to germinators with alternating temperatures of 20º-30ºC and 10 hours of light, for up to 15 days. Imbibition curves were determined under the conditions 30ºC, 20º-30ºC/10 hours of light and 30º-20ºC/10 hours of light. The X-ray protocol that best allowed viewing of internal seed structures was 30Kv for 45 seconds. Seed separation using the blower setting at a 3.0 opening for 30 seconds raised the number of embryonic seeds to values exceeding 99%, also raising the germination rates as a consequence. The imbibition pattern is three-phased and the germination process is completed in 72 hours. Under alternate temperatures, primary root growth is favored.